Epigenetic modifications potentially controlling the allelic expression of imprinted genes in sunflower endosperm - Zhichao Zhang (BMC, 2021)
Abstract Background Genomic imprinting is an epigenetic phenomenon mainly occurs in endosperm of flowering plants. Genome-wide identification of imprinted genes have been completed in several dicot Cruciferous plant and monocot crops. Results Here, we analyzed global patterns of allelic gene expression in developing endosperm of sunflower which belongs to the composite family. Totally, 691 imprinted loci candidates were identified in 12 day-after-pollination sunflower endosperm including 79 maternally expressed genes (MEG) and 596 paternally expressed genes (PEG), 6 maternally expressed noncoding RNAs (MNC) and 10 paternally expressed noncoding RNAs (PNC). And a clear clustering of imprinted genes throughout the rapeseed genome was identified. Generally, imprinting in sunflower is conserved within a species, but intraspecific variation also was detected. Limited loci in sunflower are imprinted in other several different species. The DNA methylation pattern around imprinted genes were investigated in embryo and endosperm tissues. In CG context, the imprinted genes were significantly associated with differential methylated regions exhibiting hypomethylation in endosperm and hypermethylation in embryo, which indicated that the maternal demethylation in CG context potentially induce the genomic imprinting in endosperm. Conclusion Our study would be helpful for understanding of genomic imprinting in plants and provide potential basis for further research in imprinting in sunflower.